Bio-Efficacy Evaluation of Herbicides for Weed Management in Rabi Onion - , B.S. Gohil; , B.P. Solanki; , M.R. Kadivar; , R.R. Donga (Archives of Current Research International, 2024)
A field experiment entitled “Bio-efficacy evaluation of herbicides for weed management in rabi onion” was conducted at Weed Control Research Farm, Department of Agronomy, College of Agriculture, Junagadh Agricultural University, Junagadh (Gujarat) during the rabi season of 2021-22 on medium black calcareous soil. The experiment comprising 14 treatments was laid out in a randomized block design with three replications. The results revealed that next to weed-free treatment, tank-mix pendimethalin 450 g/ha + oxyfluorfen 120 g/ha as pre-planting fb HW at 40 DATP, tank-mix pendimethalin 450 g/ha + oxyfluorfen 120 g/ha as pre-planting fb pre-mix propaquizafop + oxyfluorfen 43.75+105 g/ha at 40 DATP and tank-mix pendimethalin 450 g/ha + oxyfluorfen 120 g/ha as pre-planting fb pre-mix quizalofop + oxyfluorfen 100 g/ha at 40 DATP control of complex weed flora, reduced population and dry matter of weeds and having less reduction in yield due to better control of weeds, less crop-weed competition, higher weed control efficiency.